Testing for Nonlinear Structure and Chaos in Economic Time. A Comment. - Cars Hommes; Sebastiano Manzan (Tinbergen Institute, 2006)
This short paper is a comment on ``Testing for Nonlinear Structure and Chaos in Economic Time Series'' by Catherine Kyrtsou and Apostolos Serletis. We summarize their main results and discuss some of their conclusions concerning the role of outliers and noisy chaos. In particular, we include some new simulations to investigate whether economic time series may be characterized by low dimensional noisy chaos.
Keywords: C22; C45; C61; 330; nonlinearity; chaos; noise; self-organized criticality; Mackey-Glass-GARCH